Biosynthetic arginine decarboxylase in Escherichia coli is synthesized as a precursor and located in the cell envelope. - Buch, J K (1985)
The biosynthetic form of arginine decarboxylase (ADC) catalyzes the synthesis of agmatine, a precursor of putrescine, in Escherichia coli. Selective disruption of the cell envelope and an assessment of ADC activity or immunoprecipitable ADC in various fractions demonstrated its location between the cytoplasmic membrane and peptidoglycan layer. Expression in minicells of the speA gene encoding ADC resulted in the production of two immunoprecipitable species (74 and 70 kilodaltons). Studies in vivo with a pulse and chase of radiolabeled amino acid into the two species suggest a precursor-product relationship. This relationship was corroborated by demonstrating the accumulation of the 74-kilodalton species in a strain of E. coli unable to process signal sequences. Peptide mapping experiments with V8 protease, trypsin, and alpha-chymotrypsin demonstrated that the two species of ADC were very similar except for a minor difference. These data were used to substantiate the compartmentalization hypothesis as to how exogenous arginine can be channeled preferentially into putrescine.